2019
DOI: 10.1590/1413-7054201943025718
|View full text |Cite
|
Sign up to set email alerts
|

Biochar association with phosphate fertilizer and its influence on phosphorus use efficiency by maize

Abstract: The use of fertilizers with some degree of protection of the phosphate ions can reduce soil adsorption and increase the absorption by plants, increasing the efficiency of phosphorus (P) fertilization. This study aimed to evaluate the performance of a phosphate fertilizer associated with biochar in granules in a P-fixing soil in a greenhouse experiment. Biochars were produced from two sources of biomass: sugarcane bagasse (SB) and wood sawdust (WS), which were pyrolysed at two temperatures (350 °C and 700 °C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…To eliminate the interference of phosphorus and other elements in the determination of silicon, organic acids, such as tartaric and oxalic acids, are generally added (Nolla et al, 2010). In the phosphorus analysis, ascorbic acid is used as a reducing agent for the phosphate reaction with molybdate in an acid medium (Santos;Silva;Griebeler, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the interference of phosphorus and other elements in the determination of silicon, organic acids, such as tartaric and oxalic acids, are generally added (Nolla et al, 2010). In the phosphorus analysis, ascorbic acid is used as a reducing agent for the phosphate reaction with molybdate in an acid medium (Santos;Silva;Griebeler, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…According to Santos et al (2019), although the associations of biochars with soluble phosphate fertilizers increases the soil phosphorus availability, does not always provide greater use efficiency of this nutrient by the plants, which implies, according to the authors, that other strategies should be adopted in order to increase the uptake and utilization of phosphorus by crops on soil amendment with biochars. Lowercase letters in the row compare each control treatments with each of the doses of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…This fact confers to biochar an evident liming potential [2,27]. This effect, as well as the effects of crop P-use efficiency, has been described in many studies [17,18]. Other studies have suggested that these effects can be mediated by the high adsorption capacity of biochar [15,28].…”
Section: Discussionmentioning
confidence: 83%
“…Thus, in acidic soils, Pi is adsorbed in Al/Fe oxides, and in alkaline soils, Pi is precipitated through Ca bond. Different authors have described the effects of biochar on P bioavailability [15,16], the soil P fraction related to P plant availability [17], the efficiency of P use by plants [18], mycorrhizal colonization [19], and indeed, changes in phosphate crystalline structures [20]. Moreover, this effect could be increased by a large number of carboxylic groups and high surface adsorption area that different biochars normally show.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation